Effect Special Exercises & Electrical Muscle Stimulation in Maximum Strength Balance by indication Electrical Activity for Muscles on Both Sides of Body For Disabled Weightlifters - Kadhim, Ali; Gassim, Mouyad (Journal of Physical Education, 2019)
The study aimed to identify the differences in the values ​​of the maximum strength according the electrical activity of some muscles working on both sides of the body in the (Bench Press) for the disabled, and to identify the effect of special exercises and electrical stimulation in the balance of maximum strength on both sides of the body of some the muscles working in(Bench Press), The researcher used the experimental method on (4) Weightlifters of the Iraqi team of the disabled in Baghdad, and were chosen by deliberate method, and different categories of weight (49 kg), (65 kg), (88 kg), (107 kg), (100%) of the research community. The researcher used EMG during the performance of (Bench Press) and strongly(90%) of the maximum achievement, and it was measured the activity of the electrical(Pectoralis Major muscle, Anterior Deltoid muscle, and Triceps Brachii muscle) to the right side and to the left side, and the according of the results The Researcher Concluded: that the use of electromyography is a successful and accurate method for measuring muscle strength to diagnose the strengths and weaknesses of muscle groups that affect performance. Also, the use of special exercises with electrical stimulation leads to the development of maximum strength especially for weaker muscles to approach their values ​​of stronger muscles to improve muscle balance. The side of the body, which is reflected positively on performance and thus on achievement. And the researcher recommended a number of recommendations, including the necessity to use modern devices in detecting imbalance in muscle work, especially the balance of the maximum strength of muscles on both sides of the body in the(Bench Press), and the necessity to use exercises associated with electrical stimulation to the work of a training system includes the benefits of both exercise And electrical stimulation, to develop maximum strength and improve muscle balance on both sides of the body.